African spirituality: forms, meanings, and expressions - Olupona, Jacob K. (Crossroad, 2000)
What is Pa divination in Nigeria? Who or what is Mami Water? Does a single African spirituality exist across all indigenous cultures, even after their contact with Western religions such as Christianity? In this illustrated book, a perfect introduction to the fascinating world of African religion, spirituality, and cosmology, writers from Margaret R. Miles and Kathleen O'Brien Wicker to Ogbu Kalu and Abdulkader I. Tayob lead us into discussions of the diversity of African spiritual traditions and the forms and patterns that link them. Special topics include Dagbamba, Haitian Vodun, shrines, divination, candomble, and Sufism and the role of Islam.
Keywords: Africa – Religion; Anthropology/Ethnology; Other Religions; Spirituality/Spiritual Life/Mysticism